Vaccines against cancer. (17th April 2014) - Hunter, Philip
<x xml:space="preserve">Abstract</x> New knowledge and new technologies could bring a much‐needed breakthrough for the development of therapeutic vaccines to fight cancer. <boxed-text content-type="graphic" id="embr201438780-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>